‘Guidance' or ‘Misleading'? The government subsidy and the choice of enterprise innovation strategy - Ding, Jian; Wang, Jiaxin; Liu, Baoliu; Peng, Lin (Frontiers in Psychology, 2022)
Government subsidies have a direct impact on firms' innovation strategies. The game relationship between the government, the subsidized firm and its competitors under different subsidy strategies affects firms' innovation behavior and thus innovation performance. This paper uses a dynamic evolutionary game theory approach based on cost-benefit differences to analyse the mechanisms by which government subsidy strategies affect firms' innovation strategies. It is found that the marginal benefits of a firm's innovation strategy will directly affect the game outcome, indicating that the choice of innovation strategy depends on the maximization of individual firm's interests. At the same time, a firm's innovation strategy is influenced by the firm's own innovation ability and competitors' innovation strategy, and there are two game equilibria. Government subsidies have a positive contribution to the innovation strategy choice of subsidized firms, but have a crowding-out effect on non-subsidized competing firms. The strength of the penalty (the efficiency of the implementation of government subsidies), the marginal revenue of the subsidized firms' rational use of government subsidies and the competitors' strategic choices will directly affect the game outcome.